The Persistence of Islamist Political Parties in Bangladesh: A Rational Choice Argument - Hajjaj, Bobby (Journal of Asian and African studies, 2025)
In 1971, the new country of Bangladesh was carved into the world political map. The country’s first government identified it as a secular nation primarily due to the religious identity averred by the Pakistani state apparatus, its former oppressor. Over half a century after its independence, the country has seen a considerable impact of religion in politics, with many academic publications on Islamist movements and politics since the early 2000s. A conspicuous gap in this literature is the lack of focus on Islamist political parties, even though all Islamist political movements emerged from within those parties. This paper argues that the continued existence of Islamist parties is due to two specific factors: institutional change and large madrasa networks. This paper adopts a ‘rational choice’ approach to investigate these two factors critically.